1998
DOI: 10.1111/j.1439-0450.1998.tb00820.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vaccination againstMycoplasma hyopneumoniaein Pig Herds with a Continuous Production System

Abstract: Wtb 7 bbkrsummary An inactivated M F p h a &peumnizc vaccine was evaluated in five pig herds clinically infected with enzootic pneumonia and practising a continuous production system in the growmg/finishmg unit. In each herd, a vacanated and control group of approximately 47 pigs each were individually monitored from birth until slaughter. Vaccinated pigs received the first dose at about 1 week of age and the second approximately 3 weeks later. During all production stages, an equal number of vaccinated and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
2
35
1
2
Order By: Relevance
“…The percentage of mortality during fattening showed a statistically significant difference in favour of vaccinated animals, a result which was not obtained in other field studies using the same vaccine [10,11].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The percentage of mortality during fattening showed a statistically significant difference in favour of vaccinated animals, a result which was not obtained in other field studies using the same vaccine [10,11].…”
Section: Discussioncontrasting
confidence: 80%
“…Besides the above differences, the study described here is based on a much larger number of pigs (13691) than that used in other experiments [1,2,[10][11][12]. The study, which was carried out in a pig-rearing company, also takes into account the different systems which are used in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is a very common control measure which has been extensively proven to reduce performance losses, the severity of clinical signs and lung lesions (Maes and others 1998, 1999, Jensen and others 2002, Wilson and others 2012, Del Pozo Sacristán and others 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In comparison, Step et al (2008) observed no differences in HCW between weaned cattle vs. weaned and vaccinated or nonbackgrounded (no wean or vaccination history) cattle. Maes et al (1998) showed no significant differences (P = 0.4116) in carcass traits between vaccinated and unvaccinated pigs. This study shows little effect of antibody level or responses to vaccination with traditional carcass quality traits, supporting the concept that increased antibody levels do not have deleterious consequences on carcass quality.…”
Section: Response To Vaccination Trait Effects On Carcass Quality Traitsmentioning
confidence: 97%